NUMERIK WARNA KAIN SEBAGI LAMPUNG - Susyanti, Susi (Universitas Mercu Buana, 2025)
Detecting Colors in Lampung's Sebagi Fabric and Converting them to Color Codes. The methodology employed in this study is qualitative ethnography, with data collection conducted through direct field surveys and color detection using the SCI D65 10° Colorimeter. The colorimeter detects the surface colors of Sebagi fabric, converting them into Lab values, which are then translated into RGB, CMYK, and HEX color codes through the Nixsensor application. The primary findings indicate that three Sebagi fabrics were successfully identified and assigned color codes, providing a valuable reference for textile, product, and graphic designers, as well as researchers. The study concludes that using a colorimeter yields accurate results for fabric color detection after conversion. The color data collected from Sebagi fabric at the Lampung Museum in 2022 can serve as a valuable reference for documentation and culturally based design development in the digital and manufacturing era.